Differential resource and service needs of children in Edo State public libraries (2007)
The children library's resources and service in Edo state public library vary according to the location. The categories of the libraries are; urban area libraries(UAL), sub-urban area libraries(SAL) and rural area libraries (RAL). The difference in the resources and services indicated that resources and services are not evenly distributed in the state.